Método Montessori en el desarrollo de las competencias matemáticas de cuarto grado de la Escuela Dr. Edison Calle Loaiza, Loja 2023 - Torres Álvarez, Andrea Ximena (2023)
This research paper analysed the impact of the Montessori teaching method on the development of mathematical competencies in fourth grade students from the Dr. Edison Calle Loaiza School. The research focused on three specific objectives: to diagnose students' mathematical skills, to design a pedagogical proposal based on the Montessori method, and to evaluate its impact on the development of these skills. It is a descriptive with a non-experimental design type of study, with a mixed approach that made it possible to show the impact of the Montessori method on mathematical competences; different methods were used, such as: scientific, analytical, synthetic, inductive, descriptive; the techniques used were: prior and subsequent evaluation, and the interview; the instruments were: pre- and post-evaluation questionnaire, structured questionnaire; the sample population consisted of 25 students and a teacher; the established procedures were for the diagnosis, theoretical foundation, data tabulation, analysis and interpretation of results, elaboration of discussion, conclusions, recommendations and the approach of the educational improvement plan. The pedagogical plan based on the Montessori method was implemented in the classroom and evaluated through a post-test, the results demonstrated a significant improvement in the mastery of mathematical skills. Most students were able to successfully understand and apply the required concepts and skills, highlighting the effectiveness of the Montessori method compared to traditional approaches. The research provides a solid foundation for future research and educational practices that seek to promote more effective and meaningful learning in the context of primary education. Key words: Montessori method, mathematic competencies, learning, skills.